Improving Nursing Performance Quality in CPCR: A Cooperative Action Research Study - Mohsen Shahriari (Journal of Global Pharma Technology, 2017)
Introduction: cardiopulmonary arrest is the major factor beneath many deaths in world every hour, which nurses can save more lives with fast and correct CPCR. All studies showed that Survival rate and outcome of CPCR correlates closely with performing the process fast and correctly. Hence, this research was designed and carried out to improve nursing performance quality in CPCR.Materials and Methods: this is a cooperative action research study using repeated cycles as Kemmis plan (plan, administration, evaluation & reflecting) in Motahari hospital affiliating with Jahrom university of Medical Sciences-2013-2014. 50 practitioner nurses participated in the study and were assessed by ER head nurse (1-week observation, pre-test knowledge and practice by questionnaire and OSCE test). Planning was done by 10 participants including staff and head nurses in 2 theory and clinical phases for 6 months. European Resuscitation Council and American heart association Guidelines has been used. Education was done in the form of workshop (6 nurses) for 10 groups, 70 sessions (2-4 hours), every group 6-8 sessions. Paired T-test was used to determine statistical significance in evaluation phase. This plan was changed, refined and developed through reflection phase.Findings: Mean of OSCE pre-test and post-test were (.3244) and (.9306), respectively, so that Paired samples T test (p=0.0001) revealed that there was a significant difference between them. Mean of theory pre- and post-test quiz were (.5093) and (.9181) respectively, so that Paired samples T test (p=0.0001) revealed that there was a significant difference between them.Conclusions: it appears that a comprehensive and operational plan by participant on the basis of their actual need is more effective than any other CNE plans. According to the results of this research, this method for CPCR education this method for CPCR education in all hospitals affiliated to Jahrom university medical sciences.Keywords: Action Research, Nursing, Cpcr, Quality